2011
DOI: 10.1177/0748233711427053
|View full text |Cite
|
Sign up to set email alerts
|

Impact of aqueous doash extract on urinary mutagenicity in rats exposed to heterocyclic amines

Abstract: Doash (Origanum majorana) is an herbaceous plant found commonly in Saudi Arabia. It is used as a food flavor and a folk remedy to treat a number of diseases. The 2-amino-3-methylimidazo[4,5-f] quinoline (IQ) and 2-amino-1-methyl-6-phenylimidazo[4,5-b]pyridine (PhIP) are the most abundant of the heterocyclic amine carcinogens present in cooked food. In the present study, the potential of doash tea to influence carcinogen metabolism was investigated indirectly using heterocyclic amines as model mutagens, IQ and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 16 publications
0
4
0
Order By: Relevance
“…Indeed, Khan et al [12] proposed that reducing the availability of the genotoxic metabolites of chemical carcinogens from the body, by forming more water soluble conjugates, will consequently decrease the chance of an interaction with DNA through adduct formation that may lead to cancer.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, Khan et al [12] proposed that reducing the availability of the genotoxic metabolites of chemical carcinogens from the body, by forming more water soluble conjugates, will consequently decrease the chance of an interaction with DNA through adduct formation that may lead to cancer.…”
Section: Resultsmentioning
confidence: 99%
“…O. majorana essential oil was also able to partially prevent the ethanol-induced decline in sperm quality, testosterone levels, and the weight of reproductive organs in male rats [2]. Previous studies have reported the potential use of O. majorana ethanolic extract as anticancer agent [10, 11], whereas the tea extract has been shown to have immunostimulant, antigenotoxic and antimutagenic properties [3, 12]. These activities are attributed to the chemical composition, which is characterized as rich in flavonoids and terpenoids [13].…”
Section: Introductionmentioning
confidence: 99%
“…The doses utilized in our study were chosen from extensive published cancer bioassays, where in vivo genotoxicity has been extensively studied as adverse outcomes. An extensive review of the literature (more than 70 studies examined; condensed citation list reported here), found that in rodents, the typical dose of PhIP administered via gavage in rats ranged from 5 to 200 mg/kg body weight (bw) daily, while the frequency might vary from a single dose to every other day for 10 weeks (Hikosaka et al , 2004; Inaguma et al , 2003; Khan et al , 2013; Naito et al , 2004). To examine acute toxicity of PhIP, we chose two doses: 100 and 200 mg/kg bw.…”
Section: Methodsmentioning
confidence: 99%
“…Previous studies have reported the potential use of the O . majorana ethanolic extract as an anticancer agent [ 22 , 23 ], while the tea extract has been shown to have immunostimulating, antigenotoxic and antimutagenic properties [ 24 , 25 ]. These activities are attributed to the chemical composition, characterized as rich in flavonoids and terpenoids [ 26 ].…”
Section: Introductionmentioning
confidence: 99%